Rancang Bangun Alat Praktikum Gerak Lurus Berbasis Arduino Atmega 2560 Menggunakan Sensor Hc-SR04 - Dayang Nur Aqilah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Physics practicum at the secondary level still relies on conventional tools such as ticker timers, which are limited in accuracy and require lengthy data processing. This study aims to design a Uniform Linear Motion (ULM) and Uniformly Accelerated Linear Motion (UALM) practicum tool based on Arduino ATmega2560 using the HC-SR04 sensor, and to analyze its performance in measuring motion data. The tool integrates three HC-SR04 ultrasonic sensors as automatic time detectors, an LCD I2C display, a 4×4 keypad, and Microsoft Excel Data Streamer. Calibration results showed an overall average error of 2.56% with R2 = 0.99997, yielding an accuracy of 97.44%. ULM testing produced a constant velocity averaging 0.2526 m/s, while UALM testing showed increasing accelerations of 0.7916 m/s2, 1.4479 m/s2, and 1.7787 m/s2 at inclination angles of 10°, 15°, and 20°, respectively. The conclusion is that this practicum tool can accurately distinguish ULM and UALM characteristics, and is suitable for use as an interactive physics learning medium.
:: Finalisasi file repositori 21 Juli 2026_Kurnadi
Keywords: Arduino ATmega2560; HC-SR04 sensor; Uniform Linear Motion; Uniformly Accelerated Linear Motion; physics practicum tool.